A falência seletiva do Plano Diretor de Fortaleza - Pequeno, Luis Renato Bezerra (2021)
The city of Fortaleza (Northeastern Brazil) enacted a Participatory Master Plan (PMP) in 2009, targeted at a progressive urban agenda. However, after a 10-year term, the resumption of the urban agenda by the real state sector became evident: amendments to the Plan have enhanced advantages to civil construction in strategic areas for land value increase, especially where there is private interest in high-rise building development. In addition, such amendments have had negative effects on social inclusion in the city and on the protection of urban landmarks. PMP’s asymmetrical regulatory failure is related to contradictions in its enforcement, supported by new regulations for urban space commodification. We present, in this article, the strategies that adjusted the legal framework of urban planning to the demands of real estate capital, using the category “deregulated regulation” proposed by Aalbers (2016).